Isolation of Silk Proteins from a Caddisfly Larva, Stenopsyche Marmorata (Journal of Fiber Bioengineering and Informatics, 2012)
The protein composition of the silk gland of caddisfly larva, Stenopsyche marmorata was investigated.Dissected silk glands of the larvae were treated in a Tris buffer (pH 8.0) containing 8 M urea, and theproteins in the lumen of the silk gland were solubilized by freeze and thaw. The major proteins of the silkgland were precipitated upon dialysis against diluted acetic acid. The precipitate was dissolved in a basicTris buffer containing high concentrations of urea and dithiothreitol. Trypsin-like proteinase activity wasdetected in the silk gland extract. Therefore, all extraction procedures were re-visited in the presenceof Leupeptin, which is a specific inhibitor of the trypsin-like proteinase in the silk gland. The improvedpreparation of the silk gland extract contains a high molecular weight protein, namely S. marmoratasilk protein-1 (Smsp-1), of which the molecular weight was estimated as 310-320 kDa on the basisof electrophoretic mobility on cetyltrimethylammonium bromide-poly (acryl amide) gel electrophoresis.Subsequent gel filtration exhibited a chromatogram, where the Smsp-1 bands were found from void(ca. 2000 kDa) toward the 300 kDa region, latter of which corresponds to the estimated molecularweight of monomeric Smsp-1. The Smsp-1 eluted near void region was found to be electrophoreticallyhomogenous, suggesting that Smsp-1 molecules associate in a multimeric form. Sodium dodecylsulfate-PAGE indicated that the fractions eluted at the 650-280 kDa region also contain Smsp-1, together withthree kinds of low molecular weight proteins, which were designated as Smsp-2 (26 kDa), -3 (21 kDa),and -4 (16 kDa). These results suggest that the Smsps-1, -2, -3, and -4 can form a larger complex to bespun into net threads.
Keywords: Stenopsyche marmorata; Silk gland proteins; Protein composition analysis; Isolation